Impact of different antibiotic treatments on pregnancy maintenance in Holstein Friesian cows infected with foot-and-mouth disease - Vensko Zico Dandi Wahyu Pratama; Jola Rahmahani; Herry Agoes Hermadi; Nusdianto Triakoso; Kadek Rachmawati (Ovozoa: Journal of Animal Reproduction, 2025)
This study was conducted at Setia Kawan dairy cattle farming cooperative in Nongkojajar, Pasuruan, East Java to evaluate the effects of different antibiotic treatments on pregnancy sustainability in Holstein Friesian (HF) dairy cows infected with foot and mouth disease (FMD). The objective was to identify which antibiotics have minimal impact on pregnancy outcomes in FMD infected cows. A total of 106 pregnant HF cows infected with FMD were included in this study. Samples were selected using a purposive sampling method with inclusion criteria of pregnant HF dairy cows that tested positive for FMD. Four types of antibiotics were assessed, including enrofloxacin, oxytetracycline, amoxicillin, and penicillin-streptomycin. The results showed that among cows treated with enrofloxacin, 88.46% maintained pregnancy while 11.54% experienced abortion. For oxytetracycline, 73.08% of cows did not abort, whereas 26.92% did. In the amoxicillin group, 61.54% maintained pregnancy and 38.46% aborted. For penicillin-streptomycin, only limited data were available, with 23.07% maintaining pregnancy and no recorded cases of abortion. In conclusion, while variations were observed among different antibiotic treatments, statistical analysis indicated no significant association between antibiotic type and abortion rate in HF cows infected with FMD. Further studies with larger sample sizes are recommended to confirm these findings.